Pharmaceutical subsidy policy in Iran: a qualitative stakeholder analysis - Alireza Olyaaeemanesh; Ebrahim Jaafaripooyan; Akbar Abdollahiasl; Majid Davari; Seyyed Meysam Mousavi; Mansoor Delpasand (BMC, 2021)
Abstract Background Over the past three decades, allocation of foreign currency subsidies has been the primary strategy of various administrations in Iran to improve access to medicines. This strategy has resulted in several challenges, including stakeholder conflicts of interest. Objective To identify the power, interest, and role of the stakeholders in allocating foreign currency subsidies to medicines in the Iranian health system. Methods In this qualitative study, 39 semi-structured interviews were conducted. Key informants were recruited using a purposive sampling technique. The theoretical framework adopted by Varvasovszky and Brugha was employed. The data were analysed using directed content analysis. Results The foreign currency subsidy for medicines included 21 stakeholders in five main categories: governmental organizations, Iranian Parliament, general population, nongovernmental organizations (NGOs), and the pharmaceutical industry. Stakeholders varied in their level of participation and support in the policy-making process. Among them, the Iranian Government, Planning and Budget Organization, the Ministry of Health and Medical Education (MoHME), and Iran Food and Drug Administration (IFDA) were the most important stakeholders, with highly supportive positions, while domestic drug manufacturers were the strongest opponents of this policy. The Government of Iran is the most powerful institution with regard to the ability to allocate foreign currency subsidies to medicines, followed by the MoHME and the IFDA. Conclusion This study demonstrated that identifying and analysing the stakeholders involved in allocating foreign currency subsidies to medicines can provide valuable information for policy-makers to enable a more comprehensive understanding and better capacity to determine whether or not to eliminate these subsidies. Moreover, decision-making in this process is a long-term issue that requires consensus among all stakeholders. Because of the political and social consequences of eliminating foreign currency subsidies, the necessary political will is not institutionalized. We recommend a step-by-step approach in eliminating foreign currency subsidies if the requirements are met (i.e., those related to the consequences of such interventions). Therefore, revision of the current policy along with these requirements, in addition to financial transparency and enhanced efficiency, will facilitate progress towards achieving the Sustainable Development Goals by improving access to medicines.